An enhanced induction programme for general practice specialty training: a qualitative study of trainee perceptions and experience. Issue 2 (4th March 2017) - Anderson, Caroline; Lee, Kenneth; Wakeling, Judy; Bowie, Paul
Abstract: Background: Following a Judicial review brought by the British Association of Physicians of Indian Origin, greater expectation is now being placed upon Health Education England Local Offices and Deaneries across Scotland, Wales and Northern Ireland to identify doctors who may go on to experience difficulties in general practice specialty training – and who may benefit from educational support at an early stage. NHS Education for Scotland West region has offered an enhanced induction programme for trainees who were identified as being at risk of difficulty in training.Aims: To capture the experience of an enhanced induction programme; exploring insight towards potential difficulties in training; and the feelings relating to being identified as a trainee at risk of difficulty.Method: Interviews with trainees who attended the enhanced induction programme. Transcripts were analysed by a basic thematic analysis approach.Results: All non-UK Doctors completed 17 interviews. The term 'at risk' was accepted and the intervention was well received. Participants showed insight into the common areas of difficulty in trainees. The workshops helped to develop understanding of cultural differences, use of the ePortfolio, and gave participants an opportunity to practice their communication skills.Conclusions: This enhanced induction programme has provided targeted training to a group of trainees identified at risk of difficulty.